Postoperative nausea and vomiting and recovery of heart rate variability following general anesthesia with propofol or sevoflurane: a randomized, double-blind preliminary study - Ahn, Hyoeun; Chae, Yun Jeong; Kang, Seyoon; Yi, In Kyong (Frontiers in Medicine, 2025)
PurposePostoperative nausea and vomiting (PONV) remain significant complication after general anesthesia. Inhaled anesthetics are a known risk factor for PONV. Heart rate variability (HRV), an indicator of autonomic nervous system balance, is influenced by anesthetic agents and may be linked to PONV. This study aimed to compare HRV dynamics and their relationship with PONV between sevoflurane and propofol anesthesia.MethodsThis preliminary randomized double-blind study included 40 adult participants aged 20–60 years, with the American Society of Anesthesiologist Physical Status I or II, scheduled for elective breast surgery; the participants were randomly assigned to sevoflurane or propofol group. HRV was measured preoperatively and postoperatively, in the post-anesthetic care unit. Incidence (defined as the presence or absence of any PONV during the study period), severity (0–3 points), PONV impact scale, and patient satisfaction, were recorded postoperatively at 30 min, 3 h, and 1 and 2 days.ResultsThere was no significant intergroup difference in demographics, type of surgery, anesthesia duration, and Apfel score. The sevoflurane group had a higher PONV incidence than the propofol group; significant intergroup differences in the PONV profile were mainly observed <30 min postoperatively in PONV frequency and severity and nausea severity. Although there was no significant intergroup difference in preoperative and postoperative frequency-domain parameters, total power (Ln), LF, LF (Ln), and HF (Ln), decreased postoperatively in the sevoflurane group.ConclusionSevoflurane use was associated with more frequent, severe PONV <30 min postoperatively than propofol use, without differences in HRV dynamics. With sevoflurane use, HRV parameters did not recover to preoperative levels and were potentially associated with PONV.